2019
DOI: 10.1055/a-0829-6990
|View full text |Cite
|
Sign up to set email alerts
|

Die Rolle Der Psychotherapie Beim Reizdarmsyndrom

Abstract: ZusammenfassungDas Reizdarmsyndrom ist eine häufige funktionelle gastrointestinale Störung, die aufgrund wiederkehrender gastrointestinaler Beschwerden wie Bauchschmerzen oder Stuhlveränderungen die Lebensqualität erheblich beeinträchtigen kann. Basierend auf dem biopsychosozialen Krankheitsmodell wird die Ausprägung des Reizdarmsyndroms durch die Kombination von veränderten physiologischen Prozessen, sozialen Aspekten und psychischen Faktoren beeinflusst. Während der Fokus bisher auf der Linderung der Darmbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…The limited success of medical treatments for IBS has led to the emergence of various psychological therapies ( Guthrie et al, 1993 ; Hetterich and Stengel, 2020 ). Meanwhile, multiple systematic reviews and meta-analyses have demonstrated the significant efficacy of psychotherapy in improving IBS symptoms and daily functioning ( Laird et al, 2016 , 2017 ; Weibert and Stengel, 2019 ; Shah et al, 2020 ). For instance, psychodynamic therapies provide a well-defined framework for addressing the unconscious emotional processing that plays a central role in MUS, and they have been further refined based on neuroscientific findings ( Cooper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The limited success of medical treatments for IBS has led to the emergence of various psychological therapies ( Guthrie et al, 1993 ; Hetterich and Stengel, 2020 ). Meanwhile, multiple systematic reviews and meta-analyses have demonstrated the significant efficacy of psychotherapy in improving IBS symptoms and daily functioning ( Laird et al, 2016 , 2017 ; Weibert and Stengel, 2019 ; Shah et al, 2020 ). For instance, psychodynamic therapies provide a well-defined framework for addressing the unconscious emotional processing that plays a central role in MUS, and they have been further refined based on neuroscientific findings ( Cooper et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these conventional treatments have certain limitations. Therefore, attempts have been made to understand IBS from the perspectives of psychosocial stress and the enteric nervous system [14], and accordingly, various alternative methods have been used for its treatment including dietary regulation, psychotherapy, acupuncture, and herbal drugs [15,16,17,18]. Samryungbaekchul-san (SRS, Jinryobyakujutsu-san in Kampo medicine and Shenlingbaizhu-san in traditional Chinese medicine) is a herbal formula that has been used since the Song Dynasty (AD 1107) in China.…”
Section: Introductionmentioning
confidence: 99%